DESIGNING AN INTERACTIVE DIGITAL ATTENDANCE SYSTEM WITH SCANNING BARCODES AND WHATSAPP NOTIFICATIONS FOR STUDENTS AT PRIVATE VOCATIONAL SCHOOL DWIWARNA MEDAN USING THE RAD METHOD - Utami, Tri Ulfa; Barany Fachri; Juliandri (Cattleya Darmaya Fortuna, 2026)
The rapid development of information technology has encouraged its application in various fields, including education. One of the most important administrative activities in schools is the student attendance process. However, attendance systems that are still conducted manually have several weaknesses, such as the risk of data manipulation, slow recap processes, and low efficiency in monitoring student attendance. Therefore, a more modern, effective, and accurate attendance system is needed. This study aims to design an interactive digital attendance system using barcode scanning technology and WhatsApp notifications at Dwiwarna Private Vocational High School, Medan. The system allows students to record their attendance quickly by scanning a unique barcode and provides real-time attendance information to parents or guardians through WhatsApp notifications. The system development method used in this research is Rapid Application Development (RAD), which emphasizes fast development, prototype-based processes, and active user involvement at every stage. The result of this study is a web-based attendance system that is able to improve the efficiency of attendance recording, minimize errors and fraud, and strengthen communication between the school and students’ parents. With the implementation of this system, it is expected that student attendance data management at Dwiwarna Private Vocational High School, Medan can be carried out more optimally, transparently, and accurately.